1997
DOI: 10.1111/j.1095-8649.1997.tb01625.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the assimilation of fluorescent pigments of microalgae Isochrysis galbana by the early larval stages of turbot and herring

Abstract: The appearance of large supranuclear vacuoles in the enterocytes of 1-and 4-days post-hatch larvae of turbot and herring, respectively, revealed by the pinocytotic uptake of a fluorescent marker (FITCdextran), indicates a potential for the absorption of dissolved nutrients by the endotrophic stages of marine fish larvae. Ingestion of algal cells by turbot larvae was observed soon after hatching, but low level pinocytotic absorption of algal material was first seen during the second day. More extensive lysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
2
Order By: Relevance
“…has been reported for yolk-sac larvae of Atlantic halibut (1-5% of the ingested carbon, Reitan et al, 1994a). Tytler et al (1997) reported lysis of ingested I. galbana by 2-day-old turbot larvae, and from day 3 after hatching vacuoles containing chlorophyll were observed in the enterocytes of all larvae examined. However, earlier observations on turbot larvae have suggested only limited digestion of ingested I. galbana (Howell, 1979).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…has been reported for yolk-sac larvae of Atlantic halibut (1-5% of the ingested carbon, Reitan et al, 1994a). Tytler et al (1997) reported lysis of ingested I. galbana by 2-day-old turbot larvae, and from day 3 after hatching vacuoles containing chlorophyll were observed in the enterocytes of all larvae examined. However, earlier observations on turbot larvae have suggested only limited digestion of ingested I. galbana (Howell, 1979).…”
Section: Discussionmentioning
confidence: 69%
“…In the early feeding period the larvae have the opportunity to ingest both microalgae and bacteria, which are present together with the prey. Both, the ingestion of microalgae by the larvae (Reitan et al, 1994a;Tytler et al, 1997) and the microbial colonization of the young larvae (Bergh, 1995;Skjermo, 1996) are believed to be fundamental for the viability of the larvae. However, so far little is known about the process determining the colonization of the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and size of the screened microalgae do not appear to play a significant role in the ingestion preferences of the mangrove cockle larvae, based on epifluorescent microscopy. The usefulness of epifluorescent microscopy for the selection of microalgae species at different stages of the larval was already being proved to be effective in similar studies with gastropod mollusks (Aranda et al, 1991), echinoderms (Duy et al, 2015), fish (Tytler et al, 1997) and crustaceans (García et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Ещё в ранних экспериментах было обнаружено повышение скорости роста и выживаемости личинок тюрбо при питания коловратками с добавлением примнезиофитовых микроводорослей Isochrysis galbana . Позднее (Tytler et al, 1997) обнаружил, что личинки вскоре после выклева, еще во время эндогенного питания, потребляют клетки I. galbana и выявил даже низкую абсорбцию (путем пиноцитоза) клеточного материала микроводорослей (пигментов) в заднем кишечнике.…”
Section: роль микроводорослей при питании личинок живыми кормамиunclassified